2019
DOI: 10.3389/fchem.2019.00015
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Small Molecule p53 Stabilizer for Brain Cell Differentiation

Abstract: Brain tumor, as any type of cancer, is assumed to be sustained by a small subpopulation of stem-like cells with distinctive properties that allow them to survive conventional therapies and drive tumor recurrence. Thus, the identification of new molecules capable of controlling stemness properties may be key in developing effective therapeutic strategies for cancer by inducing stem-like cells differentiation. Spiropyrazoline oxindoles have previously been shown to induce apoptosis and cell cycle arrest, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The modified compound spiropyrazoline oxindole 1a was tested on the glioma cell line GL-261, alone and in combination with TMZ. These studies revealed an effective reduction in stemness through the reduction of the SOX2 protein levels, thereby promoting chemotherapy sensitization (149). Other spirooxindoles entered clinical trials and have been or are being studied in patients with advanced solid tumors and AML (MI77301(SAR405838), DS-3032b/milademetan, APG-115) (27,54).…”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified compound spiropyrazoline oxindole 1a was tested on the glioma cell line GL-261, alone and in combination with TMZ. These studies revealed an effective reduction in stemness through the reduction of the SOX2 protein levels, thereby promoting chemotherapy sensitization (149). Other spirooxindoles entered clinical trials and have been or are being studied in patients with advanced solid tumors and AML (MI77301(SAR405838), DS-3032b/milademetan, APG-115) (27,54).…”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…The synergism of combining MDM2 inhibition with chemotherapeutics has shown to be effective in AML and multiple trials are running in diverse tumor types (NCT04190550, NCT03725436, NCT03031730, NCT04113616, NCT04275518) (54). In GB, multiple pre-clinical studies have already proven that MDM2 inhibition induces chemosensitization, including Nutlin-3a, RG7112, spiropyrazoline oxindole 1a, RITA, SP-141 and SGT-53 therapy (146,149,159,160,174,217,221). Nutlin-3a enhanced antitumor activity of TMZ in a humanized intracranial patient-derived xenograft model of GB (222).…”
Section: Mdm2-chemotherapymentioning
confidence: 99%
“…The pink color in the structures highlights the side chain of the bioisosteric replacements of the 6chlorooxindole group in RO8994. Later in 2015, Ivanenkov's group reported the regioselective synthesis of a series of compounds containing the spiro-indolinone scaffold from the one-pot reaction of commercially available 2thioxoimidazol-4-one 89, sarcosine 90 and isatin 91 (Scheme 22)[132]. Such molecules were evaluated on their ability induce apoptosis and block the proliferation of HepG2, Hek293, MCF-7, SiHa and HCT116 cell lines.…”
mentioning
confidence: 99%